2011
DOI: 10.1136/bjsports-2011-090006
|View full text |Cite
|
Sign up to set email alerts
|

A new VO2maxprotocol allowing self-pacing in maximal incremental exercise

Abstract: As SPV is a closed-loop test (10-min duration) that allows subjects to self-pace their work rate, it disregards the need for experimenters to estimate starting work rates, stage lengths and increments in order to bring about volitional exhaustion in 8-10 min. The observation that the SPV may also elicit higher VO(2max) values than a traditional test warrants further research in this area and its consideration as standard measure to elicit VO(2max).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
85
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 23 publications
15
85
2
1
Order By: Relevance
“…Other studies have shown that the VO 2max measured during conventional INC may be less than that achieved when subjects are either free to choose their power outputs in free-range exercise51 52 or according to an incremental increase in their ratings of perceived exertion 17. Our study, however, differs from previous attempts in that we used subjects with high levels of aerobic capacity,30 employed a VER to confirm the attainment of VO 2max during INC 1 ,9 20 34 and chose a graded treadmill running INC test that produces the higher VO 2max values 7 10 53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that the VO 2max measured during conventional INC may be less than that achieved when subjects are either free to choose their power outputs in free-range exercise51 52 or according to an incremental increase in their ratings of perceived exertion 17. Our study, however, differs from previous attempts in that we used subjects with high levels of aerobic capacity,30 employed a VER to confirm the attainment of VO 2max during INC 1 ,9 20 34 and chose a graded treadmill running INC test that produces the higher VO 2max values 7 10 53.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have indeed shown that higher VO 2max values can occasionally be achieved either when different incremental exercise protocols are used,1315 or during testing in the heat,16 or when subjects exercise at progressively increasing rates of perceived exertion (RPE) 17. Conversely, some argue that a plateau in VO 2 is an inconstant phenomenon, consistently difficult to demonstrate and which may also occur during submaximal exercise 18 19.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior of the relationship between V O2 and the performance in the YYIR2 suggests that factors such as the ability to change direction and acceleration, which depend more on the capacity of application of the force of the lower limbs, could be determining in the performance of intermittent activities in the O20, compared to U20 players, who are more dependent on their aerobic capacity (Pasquarelli et al, 2010). Ahmaidi et al (1992), suggest that the differences in the values obtained in the different tests could be related to biomechanical factors and the energy expenditure efficiency, possibly because of the recruitment pattern of fibers, being more efficient for a specific intensity task, and a higher recruitment of type I fibers than type II (Mauger and Sculthorpe, 2012). This suggests that it is insufficient to consider just V O2max as the only variable to qualify performance in high-intensity, intermittent activities (Ueda et al, 2011;Denadai et al, 2004;Bassett and Boulay, 2000).…”
mentioning
confidence: 87%
“…Podobné uvažovanie nachádzame i v štúdií (Ansley, Robson, St Clair Gibson, & Noakes, 2004), kde autori poukazujú na fakt presného poznania časovej dĺžky zaťaženia v zmysle optimalizácie pohybového výkonu. Ďalším, vzhľadom k našej práci podstatným potvrdením, sú výsledky práce (Mauger & Sculthorpe, 2012), kde autori porovnávali na skupine 16 netrénovaných študentov (22 ± 7 rokov; telesná výška 1,75 ± 0,1 m; telesná hmotnosť 78 ± 16 kg) dva typy protokolov. Prvý test pozostával zo stupňo-vaného protokolu (každý stupeň 2 minúty) s iniciálnou záťažou 60 W. Test bol ukončený pri subjektívnom dosiahnutí maxima alebo pri situácii poklesu kadencie < 60.…”
Section: Dizajn Testovacieho Protokoluunclassified